Impact of cleansing protocols to remove endodontic sealer residues on the adhesive interface: Bonding with universal adhesive systems - Zaniboni, Joissi Ferrari [UNESP]; de Souza, Vitor [UNESP]; Escalante-Otárola, Wilfredo Gustavo; Porto, Thiago Soares [UNESP]; Godoy, Eduardo Fernandez; Kuga, Milton Carlos [UNESP] (Wiley, 2022)
Objective: The aim of this study was to evaluate the effectiveness of cleansing protocols to remove sealer residues using different cleaning strategies and the effect of bond strength of two universal adhesives to dentin impregnated with epoxy resin-based sealer. Materials and Methods: Fifty bovine dentin specimens were impregnated with epoxy resin-based sealer containing calcium hydroxide (Sealer Plus) and submitted to cleansing protocols (n = 10): negative control (NC), positive control (PC), 95% ethanol (ET), xylol (XI), and amyl acetate (AA). Specimens were evaluated by scanning electron microscope (SEM). Other 100 specimens were submitted to the same protocols (n = 20). Each protocol was divided into subgroups (n = 10) according to the universal adhesive system used: Scotchbond Universal (SU); Ambar Universal (AU). Bond strength was evaluated by micro-shear bond test (μSBT). Persistence of residues data were assessed with Kruskal-Wallis and Dunn's tests. μSBT data were analyzed with two-way ANOVA (α = 5%). Results: ET presented higher persistence of residues compared to AA and XI (p < 0.05). AA and XI were similar from each other (p > 0.05). AU and SU presented similar μSBT values, regardless of the cleansing solution (p > 0.05). SU-NC presented the highest μSBT among all conditions (p < 0.05). Conclusion: The bond strength of universal adhesives was not affected by different amounts of sealer residues after different cleaning protocols. Clinical Significance: Non-polar substances such as amyl acetate and xylol are effective for removing residues from epoxy resin-based endodontic sealers.
Keywords: amyl acetate; bond strength; epoxy resin sealer; root canal sealer; xylol